2021
DOI: 10.3390/metabo11040235
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Between-Subject Variability in Subcutaneous Absorption of a Fast-Acting Insulin Analogue by a Nonlinear Mixed Effects Approach

Abstract: Despite the great progress made in insulin preparation and titration, many patients with diabetes are still experiencing dangerous fluctuations in their blood glucose levels. This is mainly due to the large between- and within-subject variability, which considerably hampers insulin therapy, leading to defective dosing and timing of the administration process. In this work, we present a nonlinear mixed effects model describing the between-subject variability observed in the subcutaneous absorption of fast-actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…One recent study identified a fast-acting insulin absorption by applying a two-stage method consisting of first estimating the model parameters in each subject of the population and, then, assessing the mean vector and the covariance matrix providing a measure of the population variability. 16 Covariates, that is, dependencies of model parameters on subject characteristics such as the body mass index, the height or the age of the patient, as well as correlation between model parameters are also estimated. The approach used is the nonlinear mixed effects (NLME) modeling.…”
Section: Methodsmentioning
confidence: 99%
“…One recent study identified a fast-acting insulin absorption by applying a two-stage method consisting of first estimating the model parameters in each subject of the population and, then, assessing the mean vector and the covariance matrix providing a measure of the population variability. 16 Covariates, that is, dependencies of model parameters on subject characteristics such as the body mass index, the height or the age of the patient, as well as correlation between model parameters are also estimated. The approach used is the nonlinear mixed effects (NLME) modeling.…”
Section: Methodsmentioning
confidence: 99%
“…The MI-OMM model couples the R-OMM described in Eqs. 1-3, with the descriptions of subcutaneous absorption of fast-acting insulin analogues [22], [23] (Section II-C.1), and plasma-interstitium glucose kinetics [24], [25] (Section II-C.2) (Fig 2 , panel B). The incorporation of these modules extended the usability of the R-OMM to non-hospitalized experimental settings, since it allowed describing CGM data as function of subcutaneous insulin infusion rate and the ingested amount of carbohydrates while keeping the model ability to provide parameters and variables with a clear physiological meaning.…”
Section: The Minimally-invasive Oral Glucose Minimal Model (Mi-omm)mentioning
confidence: 99%
“…1) Subcutaneous insulin absorption and plasma insulin kinetic model: The subcutaneous insulin absorption model [22], [23], coupled with a single-compartment model of insulin kinetics in plasma [26], is described by the following differential equations:…”
Section: The Minimally-invasive Oral Glucose Minimal Model (Mi-omm)mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the critically important process of SC glucose transport was described by the so-called “triangular model,” as presented in Figure 1b. 68 With this technology, any meal and insulin delivery scenario could be pilot-tested very efficiently—a 24-hour period of closed-loop control is simulated in under 2 seconds. We need to emphasize, however, that good in silico performance of a control algorithm does not guarantee in vivo performance—it only helps test extreme situations and the stability of the algorithm and rule out inefficient scenarios.…”
Section: Enabling In Silico Pre-clinical Trialsmentioning
confidence: 99%